2005
DOI: 10.1055/s-2005-861351
|View full text |Cite
|
Sign up to set email alerts
|

Objective Benefit of a 1-day Training Course in Endoscopic Hemostasis Using the “compactEASIE” Endoscopy Simulator

Abstract: A 1-day training course on endoscopic hemostasis using the compactEASIE simulator is capable of improving the performance of hemostasis procedures. Long-term effects of repeated training sessions are currently subject of collaborative studies in New York and France.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 16 publications
0
35
0
2
Order By: Relevance
“…• twenty three papers demonstrating increased development of endoscopic diagnostic and surgical (Tsai and Heinrichs, 1994;Edmond, 2002;Garuda et al, 2002;Seymour et al, 2002;Watterson et al, 2002;Wilhelm et al, 2002;Ahmad et al, 2003;Sedlack et al, 2003Sedlack et al, , 2004Strom et al, 2003;Di Giulio et al, 2004;Grantcharov et al, 2004;Uribe et al, 2004;Clark et al, 2005;Hochberger et al, 2005;Maiss et al, 2005;Matthes et al, 2005;Long and Kalloo, 2006) or other surgical skills, particularly suturing skills, (O'-Toole et al, 1999;Stefanich and CruzNeira, 1999;Summers et al, 1999;Moody et al, 2002;Chaer et al, 2006), achieved by medical students or practitioners through the use of computer based virtual reality, or haptic, endoscopic or other surgical simulators;…”
Section: Related Non-veterinary Disciplinesmentioning
confidence: 99%
“…• twenty three papers demonstrating increased development of endoscopic diagnostic and surgical (Tsai and Heinrichs, 1994;Edmond, 2002;Garuda et al, 2002;Seymour et al, 2002;Watterson et al, 2002;Wilhelm et al, 2002;Ahmad et al, 2003;Sedlack et al, 2003Sedlack et al, , 2004Strom et al, 2003;Di Giulio et al, 2004;Grantcharov et al, 2004;Uribe et al, 2004;Clark et al, 2005;Hochberger et al, 2005;Maiss et al, 2005;Matthes et al, 2005;Long and Kalloo, 2006) or other surgical skills, particularly suturing skills, (O'-Toole et al, 1999;Stefanich and CruzNeira, 1999;Summers et al, 1999;Moody et al, 2002;Chaer et al, 2006), achieved by medical students or practitioners through the use of computer based virtual reality, or haptic, endoscopic or other surgical simulators;…”
Section: Related Non-veterinary Disciplinesmentioning
confidence: 99%
“…1 Three randomized studies have demonstrated that such training improves hemostatic skills of gastroenterology fellows. [3][4][5] In the New York project, training consisting of 3 sessions over a 7-month period led to a significant improvement in the performance of all trained hemostatic techniques in comparison to a control group with clinical training only. 3 Of the 4 skills tested, the control group showed improvement in the performance of one skill only-variceal ligation.…”
Section: Discussionmentioning
confidence: 95%
“…4 A subsequent analysis of 14 American and 18 French fellows from the abovementioned studies also found that just a 1-day training improved hemostatic skills in all trained disciplines. 5 Another study showed that an intensive training involving 12 workshops was very effective among endoscopic novices. They reached comparable levels of performance as compared with GI fellows in the New York and French projects.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the randomized controlled pilot validation study of the efficacy of three serial EASIE workshops was discussed previously [36]. A similar non-randomized study was also conducted in France with similar results from a one day intensive course [111]. The Hochberger group has conducted a number of training courses using the EASIE model in other areas, including endoscopic mucosal resection (EMR), stricture management, vital staining, polypectomy, and ERCP [107,[112][113][114][115].…”
Section: Easie and Erlangen Endotrainer Modelsmentioning
confidence: 87%